Formulation and Physical Quality Evaluation of Cyperus rotundus L. Water Fraction Gel - Alfara Derista Felany; Juvita Herdianty; Devita Riafinola Andaririt; Ivan Junius Mesak; Bilal Subchan (Universitas STRADA Indonesia, 2026)
The development of topical preparations from natural ingredients requires rigorous physical quality evaluation to ensure their safety, stability, and efficacy. This study aimed to formulate and evaluate the physical quality of a gel preparation containing the water fraction of Cyperus rotundus L. at various concentrations. The water fraction of the rhizome was formulated into gel preparations with concentrations of 5% (F1), 10% (F2), 15% (F3), and 20% (F4) using Carbopol 940 as a gelling agent. The physical quality evaluation included organoleptic tests, homogeneity, pH, spreadability, adhesion, and viscosity. The results showed that all gel formulas met the established physical quality requirements. An increase in the concentration of the water fraction significantly affected the physical characteristics of the preparation, such as a more intense color, as well as an increase in pH, adhesion, and viscosity. All formulas exhibited a pH suitable for the physiological range of the skin (5.53–6.80), good spreadability (5.49–6.77 cm), and adequate adhesion (>2 seconds). It was concluded that the nut grass rhizome water fraction gel has stable and acceptable physical characteristics, making it a potential candidate for further development as a topical preparation.